Role of "Family Centered Health Educational Approach" In Improving Adherence to Diabetic and Hypertensive Medications: A Prospective Study - Dr. A. Pavan Rajesh; Dr. Chaitanya Mavuluri; Dr. Pradeep K. Ch. S. G; Dr. K Lakshmi Narayana (International Journal of Pharma and Bio Sciences, 2023)
Family is one of the vital units of society and living. It should be treated as an intervening variable, participating, contributing, and predisposing factor in the etiology, care, and treatment of physical and mental illnesses. Family-centered care (FCC) is defined as the "provision of healthcare in a partnership or recognition that family is vital in treating persons with chronic disorders. We aim to know the role of a family-centered health education approach in improving medication adherence. Objectives were assessed by taking details from family members through a questionnaire with pre-test and post-test scores. The novelty of this research was that FCC was implemented previously in certain studies. Still, studies need to use a family-centered health education approach like ours in improving medication adherence. The study was conducted in the field practice area (Kuragallu village), Guntur. As per the sample size, 127 patients were included. Patients aged 18-80 years, males and females, who were diagnosed with type 2 diabetes mellitus (T2DM) or hypertension (HTN) or both, were included in the study. All study patients and family members were given a questionnaire before implementing the "Familycentred Health Education Approach," and again after (8 months) to the same patient. Pre and post-approach scores were compared. The mean age of patients was 57.54 years, and most were females. There was a significant improvement in post approach score compared to the pre-approach score concerning medication adherence (intake of recommended dose and composition, at the right time, during travel, and checking the availability of medications in the past ten days). Using compliance aids, proper motivation &support from family proved to increase medication adherence.